Hydrophobic Properties of Calcium Carbonate Nanoparticles/ Chitosan Composite Membrane - Ding, Ming; Ni, Na (Asian Journal of Chemistry, 2012)
Calcium carbonate nanoparticles/chitosan composite membranes were prepared in situ on chitosan films by gas diffusion method. Their morphology, structure and hydrophobic properties were characterized by XRD, FTIR and SEM. The results show that facts including temperature, the ratio of calcium to magnesium have important effect on the morphology of calcium carbonate, while the later will influence the hydrophobic properties of the composite films.